Exogenous acetylsalicylic acid mitigates cold stress in common bean seedlings by enhancing antioxidant defense and photosynthetic efficiency - Ali, Barkat; Kumar, Sujon; Sui, Xiyu; Niu, Jianpo; Yang, Junqi; Zheng, Mengni; Tang, Yi; Li, Huanxiu (Frontiers in Plant Science, 2025)
Cold stress severely limits the growth and productivity of common bean (Phaseolus vulgaris L.) seedlings, particularly during early development. Exogenous application of acetylsalicylic acid (ASA) has proven to be an effective strategy for enhancing cold tolerance. This study investigates the usefulness of exogenous ASA in enhancing cold tolerance in common bean seedlings exposed to cold stress of 5°C for 12 and 24 hours, along with a control (0h). ASA treatments (1 mM and 2 mM) significantly improved critical physiological and biochemical parameters, including photosynthesis, chlorophyll and carotenoid concentrations, oxidative stress markers, malondialdehyde, electrical conductivity, total soluble proteins (MDA, EC, SP), and antioxidant enzyme activity. Under cold stress, ASA2 constantly outperformed the other treatments. Following a 12-hour period, ASA2 showed increased chlorophyll concentrations (8.88%) and augmented Chl a levels (21.25%), alongside reducing MDA by 24.96% and SP by 67.1%. After 24 h, ASA2 demonstrated a slight increase in chlorophyll (4.26%) and raised Chl a (25.33%), with a significant reduction in MDA (16.5%) and SP (68.3%). ASA1 showed enhancements, mainly in Chl b (39.89% at 12 h) and antioxidant enzymes, with notable increases in SOD (113.17% at 12 h) and POD (110.98% at 12 h). Correlation studies indicated significant positive relationships between antioxidant enzyme activity such as, superoxide dismutase, catalase, peroxidase, ascorbate peroxidase (SOD, CAT, POD, and APX) and photosynthetic efficiency. Principal component analysis (PCA) identified ASA2 as the most effective treatment for enhancing stress resilience, accounting for the largest variance in membrane integrity and reduction of oxidative stress. Network analysis further confirmed that ASA2 strengthened the connections between photosynthesis and antioxidant activity, with more resilient and interconnected nodes indicating improved stress adaptability. At 2 mM, ASA upregulated antioxidant genes (APX1, POD1, SODC) and photosynthesis genes (RbcS1, PsbS, POR), reducing cold-induced oxidative stress and preserving chloroplast function, thereby enhancing cold tolerance and crop resilience under climate stress.